2013
DOI: 10.3724/sp.j.1005.2013.01283
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of differentiation of mesenchymal stem cells by the Hippo pathway effectors TAZ/YAP

Abstract: Mesenchymal stem cells (MSCs) are pluripotent cells which can differentiate into several distinct lineages, such as chondrocytes, adipocytes and myofibers. It has been reported that the lineage-specific transcriptional factors including Runt related transcription factor 2 (RUNX2), Peroxisome proliferator-activator receptor gamma (PPARgamma) and Myogenic differentiation 1 (MyoD) may play key regulatory roles among the differentiation of MSCs. Recently, researches have confirmed that the Hippo pathway impacts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It was reported that ****LATS (inhibitory kinase of YAP) could modulate adipocyte proliferation and differentiation via hippo signaling. Although YAP regulates differentiation in many cells such as mesenchymal stem cells (Men, Piao, & Teng, 2013), epithelial progenitors (Mahoney, Mori, Szymaniak, Varelas, & Cardoso, 2014) and retinal progenitors (Asaoka, Hata, Namae, Furutani-Seiki, & Nishina, 2014), the effect of YAP on adipogenic differentiation of preadipocyte is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that ****LATS (inhibitory kinase of YAP) could modulate adipocyte proliferation and differentiation via hippo signaling. Although YAP regulates differentiation in many cells such as mesenchymal stem cells (Men, Piao, & Teng, 2013), epithelial progenitors (Mahoney, Mori, Szymaniak, Varelas, & Cardoso, 2014) and retinal progenitors (Asaoka, Hata, Namae, Furutani-Seiki, & Nishina, 2014), the effect of YAP on adipogenic differentiation of preadipocyte is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…2). The mean of inhibition rate for each group was 0.07% (25 µg/ml), 4.13% (50 µg/ml), 6.79% (100 µg/ml), 12.38% (200 µg/ml), 18.79% (500 µg/ml) and 13.63% (750 µg/ml). BQZ at concentrations of 100, 200, 500 and 750 µg/ml could significantly inhibit the proliferation of fibroblast cells (P<0.05).…”
Section: Cellular Growth Morphological Character and Cell Source Idementioning
confidence: 99%
“…Yes-associated protein (YAP), a downstream effector molecule of the Hippo signaling pathway, serves as a transcriptional coactivator and is reportedly expressed in many human malignancies [11][12][13], including breast cancer [14]. Nuclear-YAP (N-YAP) interacts with transcription factors and promotes cancer cell proliferation, while maintaining stemness and metastasis [15][16][17][18][19]. Furthermore, its nuclear abundance was reported to correlate with tumor progression and decreased survival in patients with breast cancer [20][21][22].…”
Section: Ivyspringmentioning
confidence: 99%